2018
DOI: 10.14814/phy2.13727
|View full text |Cite
|
Sign up to set email alerts
|

Diltiazem improves contractile properties of skeletal muscle in dysferlin-deficient BLAJ mice, but does not reduce contraction-induced muscle damage

Abstract: B6.A‐Dysf prmd/GeneJ (BLAJ) mice model human limb‐girdle muscular dystrophy 2B (LGMD2B), which is linked to mutations in the dysferlin (DYSF) gene. We tested the hypothesis that, the calcium ion (Ca2+) channel blocker diltiazem (DTZ), reduces contraction‐induced skeletal muscle damage, in BLAJ mice. We randomly assigned mice (N = 12; 3–4 month old males) to one of two groups – DTZ (N = 6) or vehicle (VEH, distilled water, N = 6). We conditioned mice with either DTZ or VEH for 1 week, after which, their tibiali… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 9 publications
(5 citation statements)
references
References 52 publications
0
5
0
Order By: Relevance
“…How blood pressure lowering medications impact both vascular and muscle tissue homeostasis in the LGMD2B patient population is poorly understood. Although, previous work has shown that Diltiazem, a Ca 2+ channel blocker with blood pressure lowering capabilities, can elicit partial protection in dysferlin-null tissues using acute damage models [54]. Our group has recently shown that losartan mediates its off-target, NO-protective effects on vascular tissues in a VEGFR-dependent manner [21]; a function shown to be ablated in dysferlin-deficient cells [55].…”
Section: Discussionmentioning
confidence: 99%
“…How blood pressure lowering medications impact both vascular and muscle tissue homeostasis in the LGMD2B patient population is poorly understood. Although, previous work has shown that Diltiazem, a Ca 2+ channel blocker with blood pressure lowering capabilities, can elicit partial protection in dysferlin-null tissues using acute damage models [54]. Our group has recently shown that losartan mediates its off-target, NO-protective effects on vascular tissues in a VEGFR-dependent manner [21]; a function shown to be ablated in dysferlin-deficient cells [55].…”
Section: Discussionmentioning
confidence: 99%
“…To demonstrate that damaged fibers label falsely as hybrid fibers, we followed a protocol of injurious eccentric contractions, which has been described in detail. 16 We exposed the left TA to 40 eccentric contractions (under general anesthesia; inhaled, 2-5% for induction and 1-4% for maintenance), performed in 4 sets of 10 repetitions, with 2 min rest between sets. For each eccentric contraction, the dorsiflexors were tetanically stimulated, and the foot was plantarflexed from 90 to 160°, at 300 /S.…”
Section: Methodsmentioning
confidence: 99%
“…For each eccentric contraction, the dorsiflexors were tetanically stimulated, and the foot was plantarflexed from 90 to 160°, at 300 /S. 16 The right TA served as an unexercised control.…”
Section: Methodsmentioning
confidence: 99%
“…Diltiazem, a calcium ion channel blocker, improves the contractile properties of skeletal muscle in BLA/J mice but does not appear to reduce contraction-induced muscle damage [191]. While it boosts muscle performance after eccentric contractions, it does not significantly reduce delayed-onset muscle damage.…”
Section: Diltiazemmentioning
confidence: 98%